Strategic Approaches to Define the Production Rate in Conceptual Projects of Critical Raw Materials - Lucas Zucchi Silva; Anna Luiza Marques Ayres da Silva (Resources)
Mining projects are intricate, requiring significant time and investment for feasibility studies, despite a low likelihood of reaching execution. Accurate project factors can optimize costs across the study, execution, and operation phases. This work proposes a strategic approach to define the production rate in conceptual projects of critical raw materials, based on well-established formulae from Taylor, Long, and Singer, focusing on copper, zinc, and lead. Copper and zinc are crucial for renewable energy systems and low-carbon technologies, while lead supports energy storage applications. A dataset containing mine production and mineral resources from several mine projects, gathered from a specialized global company, was used to create a production rate equation and then compared using an adherence indicator to validate the formulae. The best adherence indicator from earlier studies was 59%. Copper projects did not show good adherence to the new formulae. Zinc and lead projects showed very good results, generating three formulae with good adherence numbers (above 70%), and they can be taken as a reference to calculate the production rate of new open-pit and underground mining projects. These findings offer a reliable strategic approach for estimating production rates in early-stage zinc and lead projects, enhancing the efficiency of the conceptual study phase in mining.